Theoretical Approach by DFT in the characterization of the Zn(II) Benzoate - Patrícia Saraiva Vilas Boas de Almeida; Vitor da Cunha Baia; José Roberto da Silveira Maia; Elson Santiago de Alvarenga (The Journal of Engineering and Exact Sciences)
The condensation reaction between aminoguanidine bicarbonate and benzoic acid produced 1,2,4-triazole which, after reaction with zinc(II) chloride, led to the formation of a complex, Zn(II)-1,2,4-triazole. This complex decomposes into chloroform leading to the formation of a by-product identified by multinuclear NMR (13C and 1H) as zinc(II) benzoate. Subsequently, a theoretical study, using the Hartree-Fock and DFT methods, was applied to validate zinc(II) benzoate as a byproduct of decomposition through the calculation of the magnetic shielding tensor (NMR), as well as to address some structural characteristics of this compound since zinc compounds present a variety of geometric arrangements and coordination numbers. The theoretical result showed that Zn(II) benzoate is the by-product of the reaction and that it dimerizes in chloroform solution.